Dendromonocotyle bradsmithi n. sp. (Monogenea: Monocotylidae) from the skin of Myliobatis australis (Elasmobranchii: Myliobatidae) off Adelaide and Perth, Australia: description of adult and larva - Chisholm, Leslie A.; Glennon, Vanessa; Whittington, Ian D. (Zootaxa, 2005)
Dendromonocotyle bradsmithi n. sp. (Monogenea: Monocotylidae) is described from the dorsal skin surface of the southern eagle ray, Myliobatis australis Macleay, 1881, collected from the mouth of the Port Adelaide River, Adelaide, South Australia. Specimens of D. bradsmithi were also found on 2 M. australis specimens collected off Mandurah, Western Australia (WA) and on 1 M. australis kept in a public aquarium in Perth (AQWA),WA. Dendromonocotyle bradsmithi is distinguished most easily from the other 12 species in the genus by the morphology of the distal portion of the male copulatory organ. The anatomy of the oncomiracidium determined by examining live larvae and the distribution of the ciliated epidermal cells and sensilla revealed by silver staining are also provided.